Effects of Career Planning and University Environment Support on Property Management at Universitas Ciputra, Surabaya - Aryani, Ni Putu; Pebruanto, Dwi Sunu Widyo; Budidharmanto, Lexi Pranata; Agustina, Karina Enny; Purwadi, Kezia Victory (Universitas Ciputra Surabaya, 2023)
The increase of high-rise buildings in Indonesia is not accompanied by an increase in the professional staff who manage them. This research was conducted because of the high demand for professional staff to manage high-rise buildings. Data were collected by distributing questionnaires by purposive sampling to 92 students in semesters 3 and 5 from two majors, namely Hotel and Tourism Business Major and Interior Architecture major. Quantitative descriptive method was usedwith multiple regression analysis which tested three hypotheses with two independent variables; Career Planning (X1) and University Environment Support (X2) and one dependent variable; Career Preparation (Y). The research results prove that career planning and university environment support have a role in career preparation independently or simultaneously. Thus, it can be concluded that students state the importance of specializing in property management in order to meet professional needs as property managers.